Green human resource management and environmental knowledge: A moderated mediation model to endorse green CSR - Hameed, Rizwana; Rehman, Nabeel; Tufail, Sajid; Kiziloglu, Mehmet (Frontiers in Environmental Science, 2023)
Firms use green human resource management (GHRM) as an essential business tactic to ‘go green”. The current research analyzes an integrative model by examining the indirect impact of GHRM practices on green corporate social responsibility through a pro-environmental psychological climate and pro-environmental behavior. This study also analyzes the moderating effect of resistance to change (RTC) and environmental knowledge on the relationship between GHRM and green CSR. The data was collected through a questionnaire-based survey of 388 executives working in various organizations under the China-Pakistan Economic Corridor (CPEC). The results were analyzed through Smart PLS-3 and present that both GHRM dimensions have indirect positive effects on green CSR through the intervening role of pro-environmental psychological climate and pro-environmental behavior. The results of the study also indicated that resistance to change (RTC) has a counterproductive effect that can impede firms and their employees from fully incorporating green practices and minimizing their negative environmental impact.